Technology Acceptance Analysis Using UTAUT: A Study of QRIS Acceptance during the Pandemic - Prasetya, Denny; Rahardjo, Alexandra Rianti Grandi; Aritonang, Eva Reh Ulina; Manggalaningwang, Jody; Maharani, Nadya Ayu; Ivander, Yohanes; Mukhamadiyev, Abdinabi (Universitas Nusantara PGRI Kediri, 2024)
Background: The COVID-19 pandemic situation has compelled society to practice physical distancing. One of the government's efforts is to encourage the use of the QRIS payment method to minimize direct physical contact during transactions. Objective: The purpose of this research is to analyze the primary driving factors in the adoption of QRIS technology. The research urgency is to determine the most contributing predictor from the variables within the UTAUT model among the people of Jabodetabek. Methods: This research used the quantitative method by conducting an online survey among 384 respondents distributed across the Jabodetabek region. The sampling technique utilized was non-purposive sampling with criteria including domicile, age, reasons, frequency, and experience of QRIS usage. Conclusion: The results of the factor analysis test indicate that the performance expectancy and effort expectancy variables are combined into one variable, while the social influence variable is divided into two independent variables. The research findings reveal that the perceived risk variable is the predictor with the most significant contribution in the context of the pandemic situation. Future researchers are expected to be able to develop the research model in other contexts with different goals.